Cell-specific role of histone deacetylase 6 in chemotherapy-induced mechanical allodynia and loss of intraepidermal nerve fibers. Issue 12 (December 2019) - Ma, Jiacheng; Trinh, Ronnie T.; Mahant, Iteeben D.; Peng, Bo; Matthias, Patrick; Heijnen, Cobi J.; Kavelaars, Annemieke
Abstract : Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a serious adverse side effect of cancer treatment with no Food and Drug Administration-approved medication for its prevention or management. Using RNA sequencing analysis of dorsal root ganglia (DRG), we identify critical contributions of histone deacetylase 6 (HDAC6) and mitochondrial damage to the establishment of CIPN in a mouse model of cisplatin-induced neuropathy. We show that pharmacological inhibition of HDAC6 using ACY-1215 or global deletion of HDAC6 is sufficient to prevent cisplatin-induced mechanical allodynia, loss of intraepidermal nerve fibers (IENFs), and mitochondrial bioenergetic deficits in DRG neurons and peripheral nerves in male and female mice. The bioenergetic deficits in the neuronal cell bodies in the DRG are characterized by reduced oxidative phosphorylation, whereas the mitochondrial deficits in the nerves are due to a reduction in axonal mitochondrial content. Notably, deleting HDAC6 in sensory neurons protects against the cisplatin-induced loss of IENFs and the reduction in mitochondrial bioenergetics and content in the peripheral nerve. By contrast, deletion of HDAC6 in sensory neurons only partially and transiently prevents cisplatin-induced mechanical allodynia and does not protect against impairment of mitochondrial function in DRG neurons. We further reveal a critical role of T cells in the protective effects of HDAC6 inhibition on these signs of CIPN. In summary, we show that cisplatin-induced mechanical allodynia is associated with mitochondrial damage in DRG neurons, whereas the loss of IENFs is related to bioenergetic deficits in peripheral nerves. Moreover, our findings identify cell-specific contributions of HDAC6 to mechanical allodynia and loss of IENFs that characterize cisplatin-induced peripheral neuropathy. Abstract : Sensory neuron HDAC6 is key mediator for cisplatin-induced loss of intraepidermal nerve fibers, whereas successful prevention of mechanical allodynia involves T cells as well.